2021
DOI: 10.3389/fpsyg.2021.633351
|View full text |Cite
|
Sign up to set email alerts
|

The Search for and Presence of Calling: Latent Profiles and Relationships With Work Meaning and Job Satisfaction

Abstract: Previous studies showed inconsistent results on the association between searching for calling and its psychosocial functioning outcomes (i.e., work meaning and job satisfaction). The link of searching for calling to its psychosocial functioning outcomes may be influenced by the presence of calling because the search for and presence of calling can co-exist within individuals. Thus, the present study employed a person-centered method (latent profile analysis) to identify subgroups combining the search for and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
2
0
2
Order By: Relevance
“…Higher scores reflect teachers' stronger presence of career calling. In several previous studies, this scale has been widely used and confirmed good reliability and close association with relatedcriterion variables (e.g., intrinsic work motivation, job satisfaction, and life/work meaning; Dik et al, 2012), also in Chinese samples (e.g., Li et al, 2021;C. Zhang, Herrmann, et al, 2015).…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Higher scores reflect teachers' stronger presence of career calling. In several previous studies, this scale has been widely used and confirmed good reliability and close association with relatedcriterion variables (e.g., intrinsic work motivation, job satisfaction, and life/work meaning; Dik et al, 2012), also in Chinese samples (e.g., Li et al, 2021;C. Zhang, Herrmann, et al, 2015).…”
Section: Methodsmentioning
confidence: 69%
“…In prior studies conducted among the Western teacher sample (e.g., Gong et al, 2013), its standardized effect size was twice as large as ours. Some studies showed that Chinese traditional collectivist values are beginning to infuse more individualist concerns (e.g., Li et al, 2021; C. Zhang, Dik, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini bertujuan untuk mengetahui hubungan kedua dimensi panggilan, yaitu presence of calling dan search for calling serta bagaimana kaitannya dengan keterikatan kerja pada guru, karena kualitas mengajar seorang guru dapat mempengaruhi bagaimana kualitas pendidikan yang diberikan. Melalui penelitian ini, akan dapat dipahami dinamika kaitan kedua dimensi panggilan dan keterikatan kerja sehingga penelitian ini diharapkan dapat menjawab tantangan Li et al (2021) untuk meneliti kedua dimensi secara seimbang, mengingat dimensi search for calling masih sedikit diteliti dan memerlukan penelitian lebih lanjut.…”
Section: Pendahuluanunclassified
“…Search for a calling adalah tahap yang penting dalam mengembangkan calling seseorang dan merupakan motivasi menuju aktualisasi diri. Hal ini menunjukkan search for a calling dengan presence of calling dapat memiliki tingkat yang sama-sama tinggi (Li, F., Jiao, R., Liu, D., & Yin, H, 2021), dan merupakan dua dimensi yang juga tumpang tindih dari konstruksi calling (Dik et al, 2012). Oleh karena itu guru SMA "X" yang masih search for a calling sebenarnya sudah berada dalam tahap presence of calling juga dan tidak murni sedang melakukan pencarian (search for a calling).…”
Section: Tabel II Mean Sd Dan Korelasi Antar Variabelunclassified
“…Kekuatan presence of calling dapat mempengaruhi efek search for a calling yang sesuai dengan harapan individu. (Li et al, 2021).…”
Section: Tabel II Mean Sd Dan Korelasi Antar Variabelunclassified